South Africa judicial review of trade remedies in South Africa - Brink, Gustav Francois (Global Trade and Customs Journal, 2025)
No abstract available.
Keywords: Judicial review; South Africa; Trade remedies

Reassessing State Consent to Jurisdiction: The Indispensable Third Party Principle before the ICJ - Sparks, Tom (Nordic Journal of International Law, 2022)
Keywords: Adjudication; Advisory opinion; Certain Phosphate Lands; Chagos Archipelago; Consent; East Timor; Indispensable third party principle; International Court of Justice (icj); Jurisdiction; Monetary Gold

Global Civil Procedure - King, Alyssa S. (SSRN Electronic Journal, 2021)
A “global” civil procedure has emerged and found its way into debates over procedural reform in both international and domestic arenas. Global civil procedure includes the procedural rules, practices, and social understandings that govern transnational litigation and arbitration. A global civil procedure norm is a norm adopted across courts or arbitration providers with the purpose of making that jurisdiction or provider more competitive in attracting transnational litigation or arbitration. Global civil procedure norms are at stake in multiple present trends and debates, including model laws in commercial arbitration, the procedure of international tribunals, the debate over investment dispute resolution, the rise of courts oriented towards international litigation, and sprawling litigation spanning multiple jurisdictions and fora. On a surface level, the values reflected in global civil procedure seem to be roughly the same across jurisdictions. A common language has emerged around competition for litigation business and procedure values such as efficiency, certainty, and impartiality. Yet different legal systems do not necessarily agree on the purpose of various shared elements of global civil procedure. For democracies, for instance, the purpose of procedural reforms might be to facilitate access to justice. Other countries may favor the same reforms because they facilitate top-down administrative control of judges. Surface agreement can submerge divergent logics that may ultimately lead to very different applications of harmonized rules. This Article begins by introducing the concept of global civil procedure, who uses it, and how. Next, it considers several examples of the phenomenon including conflicts of interest rules for adjudicators, aggrega tion, and discovery or disclosure rules. Finally, it considers the limits of global civil procedure. Although the rhetoric of procedural competition can be heard across systems, procedural values do not necessarily translate both in terms of enduring divisions between legal traditions and in terms of applications by current political regimes.